2017
DOI: 10.1159/000479507
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Sex Chromosome Aneuploidy by Cell-Free DNA Testing: Patient Choice and Performance

Abstract: Objective: To study patient choice regarding testing for sex chromosome aneuploidy (SCA) and the performance of cell-free DNA (cfDNA) screening for SCA. Methods: Patient choice regarding screening for SCA and factors influencing this choice were evaluated in a single center. In a subsequent two-center study, cases that screened positive for SCA were analyzed to determine the positive predictive value (PPV) for each SCA. Results: In all, 1,957 (61.9%) of the 3,162 patients undergoing cfDNA testing opted for SCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 20 publications
(26 reference statements)
2
27
2
Order By: Relevance
“…Previous validation studies were laboratory‐funded and lacked complete clinical follow‐up and insight into patient decision‐making regarding follow‐up diagnostic testing. A few recent studies examining positive NIPT results for SCAs in the clinical setting had relatively small sample sizes (≤50) and/or had limited information on ultrasound findings and patient demographics . These studies have also largely included patients managed through a single hospital system, and thus may not be generalizable.…”
Section: Introductioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Previous validation studies were laboratory‐funded and lacked complete clinical follow‐up and insight into patient decision‐making regarding follow‐up diagnostic testing. A few recent studies examining positive NIPT results for SCAs in the clinical setting had relatively small sample sizes (≤50) and/or had limited information on ultrasound findings and patient demographics . These studies have also largely included patients managed through a single hospital system, and thus may not be generalizable.…”
Section: Introductioncontrasting
confidence: 55%
“…While previous studies have indicated that the majority of patients with a positive NIPT for a SCA elect prenatal diagnosis, our clinical experiences highlight that this may not be true for all patient populations. In our study, 88 of the 134 viable pregnancies (65.7%) declined prenatal diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such high-performance screening has been reported for both high-risk pregnancies and in the general population [4][5][6][7][8][9]. Beyond the major trisomies (21,18, and 13), cfDNA testing panels can be expanded to include sex chromosomal aneuploidies and microdeletion syndromes, but this would increase the cumulative FPR [10]. This is due to the low prevalence of some of these conditions -and, consequently, positive predictive values of less than 10% when tested [11].…”
Section: Introductionmentioning
confidence: 99%